Prevalence of Hepatitis B Surface Antigen and its Association with Anti-Hepatitis C Virus Antibodies among Pilgrims - Abdullah A. Al Ghamdi,; Mohammad Ayman A. Safi, (Journal of King Abdulaziz University: Medical Sciences, 2023)
The present study aimed to evaluate the prevalence of the asymptomatic carriers of hepatitis B surface antigen among pilgrims; to demonstrate its distribution in different nationalities, age groups, and gender. The prevalence of hepatitis B surface antigen, among 982 apparently healthy pilgrims was determined using enzyme-linked immunosorbent assay. Positive samples were confirmed by the MiniVIDAS system. Positivity rate was 4.1% and was higher in males (87.5%), age group of 40-59 years (60%) and in Nigerian pilgrims (8 pilgrims). All samples were also analyzed for antibodies against hepatitis C virus using enzyme-linked immunosorbent assay. Only one sample was positive for both hepatitis B surface antigen and hepatitis C virus antibodies. It was concluded that there was an intermediate endemicity (4.1%) with significant (P < 0.05) difference between the rate in the different age groups but not between the rate in males and females nor in nationalities. Nationalities with low frequencies of pilgrims should not be neglected as a source of infection. No association between the presence of hepatitis B surface antigen and hepatitis C virus antibodies. Performance of this study (with genotyping) on a large scale and genotyping of the 40 positive samples is recommended.